Plasmapheresis Responsive Rapid Onset Dementia with Predominantly Frontal Dysfunction in the Context of Hashimoto’s Encephalopathy - Endres, Dominique; Vry, Magnus S.; Dykierek, Petra; Riering, Anne N.; Lüngen, Eva; Stich, Oliver; Dersch, Rick; Venhoff, Nils; Erny, Daniel; Mader, Irina; Meyer, Philipp T.; Tebartz van Elst, Ludger (Frontiers in Psychiatry, 2017)
Background: Hashimoto’s encephalopathy (HE) is a rare immunological neuropsychiatric disorder characterized by increased antithyroid antibodies and mixed neurological and psychiatric symptoms. HE has been previously discussed as a differential diagnosis for rapid progressive dementia. However, most of these patients suffered from additional neurological symptoms, like ataxia or seizures. Case presentation: Here, we present the case of a 59-year-old female patient suffering rapid onset dementia with salient frontal executive dysfunction. She developed rapid onset symptoms, including apathy, verbal depletion up to a stuporous state, severe working memory deficits, evidence of primitive reflexes, disturbed Luria’s three-step test, and micturition disorder. Analysis of her cerebrospinal fluid was normal. The serum analyses showed increased antithyroid (antithyroid peroxidase and antithyroglobulin) antibodies. In the cerebral magnetic resonance imaging, supratentorial deep and peripheral white matter lesions were found; the electroencephalography showed intermittent slowing, and the [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) depicted medial and superior dorsolateral frontal hypometabolism. Several different psychopharmacological therapeutic approaches with various neuroleptics, antidepressants, and high doses of lorazepam were unsuccessful. Due to the organic alterations, including increased antithyroid antibodies, HE was suspected. Against expectations, treatment with high-dose corticosteroids proved to be ineffective and was associated with worsening symptoms. However, escalated treatment with plasmapheresis over five days led to significant improvement in all reported symptoms and in psychometric testing. The neuropsychological improvement was stable over a six-month follow-up period, and the FDG-PET normalized. Conclusion: This case report reveals that 1) HE can mimic rapid onset dementia with predominantly frontal dysfunction; 2) this syndrome can be successfully treated in the context of HE; and 3) plasmapheresis can be effective in such a disease constellation. The detection of the immunological causes of rapid onset dementia and other psychiatric syndromes is important because it opens opportunities for new, innovative immunosuppressive treatment options.